2020
DOI: 10.1021/acs.orglett.9b04584
|View full text |Cite
|
Sign up to set email alerts
|

Relay Catalysis To Synthesize β-Substituted Enones: Organocatalytic Substitution of Vinylogous Esters and Amides with Organoboronates

Abstract: Organocatalysis was shown to facilitate conjugate additions to vinylogous esters and amides for the first time. Subsequent elimination of a β-alcohol or amine provided π-conjugated β-substituted enones. Remarkably, nucleophile addition to the electron-rich vinylogous substrates is more rapid than classical enones, forming monosubstituted products. A doubly organocatalytic (organic diol and methyl aniline) conjugate addition synthesized the products directly from alkynyl ketones. Both of these catalytic transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Screening a wide variety of chiral diols as catalysts with different electronic and steric properties revealed that the presence of electron-withdrawing and bulky groups is favorable for both enantioselectivities and yields, and Cat 1 proved to be the best choice for this process in terms of both yields and enantioselectivities. Subsequent investigations on the effect of solvents led to toluene being the optimal solvent for controlling reactivities and enantioselectivities (entries [12][13][14][15][16][17][18][19]. When the reaction was conducted at 0 °C and with a prolonged reaction time of 72 h, 3aa was obtained in 88% yield and a slightly decreased ee value (entry 20 vs. entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…Screening a wide variety of chiral diols as catalysts with different electronic and steric properties revealed that the presence of electron-withdrawing and bulky groups is favorable for both enantioselectivities and yields, and Cat 1 proved to be the best choice for this process in terms of both yields and enantioselectivities. Subsequent investigations on the effect of solvents led to toluene being the optimal solvent for controlling reactivities and enantioselectivities (entries [12][13][14][15][16][17][18][19]. When the reaction was conducted at 0 °C and with a prolonged reaction time of 72 h, 3aa was obtained in 88% yield and a slightly decreased ee value (entry 20 vs. entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…The residue was subjected to column chromatography for isolation (gradient eluent: hexane/ethyl acetate) to give products 5 and 4. 5 2 : 7.8 mg, 38% yield; 1 H NMR (500 MHz, CDCl3) δ 7.51 -7.46 (m, 2H), 7.45 -7.42 (m, 2H), 7.37 -7.28 (m, 6H), 7…”
Section: Typical Procedures For Transformation Of Oxime From Dba Derivmentioning
confidence: 99%
“…Chong and co-workers developed the asymmetric 1,4-conjugated addition of alkynyl, alkenyl, and aryl boronates to α,β-unsaturated ketones using the enantiopure 3,3′-I 2 -BINOL as the chiral catalyst . In 2011, May and co-workers reported the conjugate addition reaction of alkenylboronic acids to β-indolo-enones using 3,3′-C 6 F 5 -BINOL as the catalyst, and then the nucleophiles were changed to heteroaryl and aryl trifluoroborate salts . Sugiura and co-workers have used O -monoacyltartaric acids for the 1,4-conjugated addition of alkenyl boronic acids to α,β-unsaturated ketones and dienones .…”
Section: Introductionmentioning
confidence: 99%